2020
DOI: 10.5343/bms.2019.0041
|View full text |Cite
|
Sign up to set email alerts
|

How old are giant squids? First approach to aging Architeuthis beaks

Abstract: The giant squid Architeuthis dux Steenstrup, 1857 is one of the largest and most enigmatic marine species. Its age estimation remains controversial with many estimates of maximum age ranging from 1 to 14 yrs. Successful results regarding the study of aging in cephalopod beaks for some octopod and oegopsid squids support using these structures for age estimation. We analyzed the beaks of 10 individuals, caught between 1995 and 2006, with reconstructed dorsal mantle lengths (DMLs) between 823 and 1418 mm. The b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 47 publications
0
9
1
Order By: Relevance
“…In relation to using beaks for age determination in cephalopods, it was found that the tip erosion during the feeding process may bias increment counts in the anterior region of the beak but counting the oldest increments in the dorsal area of the section prevents age underestimation (Arkhipkin et al, 2018). A simple method has been recently developed to quantify the tip erosion using the number of increments in the dorsal non-eroded region and the width of increment of the central reading region (Perales-Raya et al, 2020). Moreover, the beak microstructure of emblematic deepsea species such as the giant squid Architeuthis dux (Perales-Raya et al, 2020) (Figure 5) provided age data and a maximum lifespan estimation of around 3 years, based on rostrum sagittal sections from the lower beaks.…”
Section: Microstructure: Age Growth and Record Of Life Extreme Eventsmentioning
confidence: 99%
See 2 more Smart Citations
“…In relation to using beaks for age determination in cephalopods, it was found that the tip erosion during the feeding process may bias increment counts in the anterior region of the beak but counting the oldest increments in the dorsal area of the section prevents age underestimation (Arkhipkin et al, 2018). A simple method has been recently developed to quantify the tip erosion using the number of increments in the dorsal non-eroded region and the width of increment of the central reading region (Perales-Raya et al, 2020). Moreover, the beak microstructure of emblematic deepsea species such as the giant squid Architeuthis dux (Perales-Raya et al, 2020) (Figure 5) provided age data and a maximum lifespan estimation of around 3 years, based on rostrum sagittal sections from the lower beaks.…”
Section: Microstructure: Age Growth and Record Of Life Extreme Eventsmentioning
confidence: 99%
“…Artificial intelligence could provide a useful tool to save time and improve the detection and count of increments since it could "learn" from the images previously analysed by experienced readers. Finally, the cumulative width of the daily increments could be a potential tool to estimate growth in the wild, before capture (e.g., Perales-Raya et al (2020) for Architeuthis dux; Queirós, Bartolomé, Xavier and Perales-Raya, unpublished for M. longimana). Preliminary results on reared O. vulgaris used correlations between cumulative widths and body mass to estimate the growth in the wild, before capture (Perales-Raya, Bartolomé, Márquez, Felipe and Almansa, unpublished data).…”
Section: Future Challenges In Research In Cephalopods Beaksmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, this technique has also been applied in other cephalopod species, e.g. the octopods Megaleledone setebos (Schwarz et al 2019), Octopus maya (Bárcenas et al 2014), the sepiid Sepia officinalis (Lishchenko et al 2018) and the oegopsid squid Dosidicus gigas (Liu et al 2015(Liu et al , 2017Hu et al 2016), Ommastrephes bartramii (Liu et al 2015;Fang et al 2016), O. caroli (Agus et al 2021), Sthenoteuthis oualaniensis (Liu et al 2015;Lu et al 2022) and Architeuthis dux (Perales-Raya et al 2020). Age determination in beaks have been mainly performed in two beak regions: the rostrum sagittal section (RSS) and the inner lateral wall surface (LWS) (Perales-Raya et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Body length can range from less than 1 cm in pygmy squids (Idiosepius spp.) with short life spans, to more than 20 m in total length (including tentacles) in the giant squid (Architeuthis dux), with a lifespan of around 3 years (Wood and O'Dor, 2000;Jereb and Roper, 2005;Perales-Raya et al, 2020). Similarly, variability in egg size can range from approximately 0.5 to 80 mm, while fecundity estimates vary from one or a few dozen eggs (e.g., cirrates, Nautilus, Sepiola, and Bathypolypus) to several millions (e.g., Architeuthis and Dosidicus), depending on body size (Calow, 1987;Boyle and Rodhouse, 2005;Laptikhovsky et al, 2018).…”
Section: Introductionmentioning
confidence: 99%